The G20 and the future of the global trading system - Axel Berger; Clara Brandi (Deutsches Institut für Entwicklungspolitik (DIE), 2016)
Since the first meeting of the G20 at the leaders' level in Washington in November 2008, trade has been an integral part of their agenda. This first meeting took place at the peak of the global financial and economic crisis, which led to a strong contraction of world trade. Remembering the global economic crisis after 1929 and the following wave of protectionist measures, the G20 countries made the commitment to not erect new trade and investment barriers. In addition, the verbal commitment to the conclusion of the Doha Development Agenda – the current round of multilateral negotiations under the auspices of the World Trade Organization (WTO) – has been part of the standard repertoire of G20 summit declarations. Yet, since the last ministerial meeting of the WTO in Nairobi in December 2015, the future of the Doha Round is more uncertain than ever before. Important member states, notably the United States, declared themselves in favour of terminating the Doha Round, whereas many emerging and developing countries insist on its continuation. Dissatisfied with the slow progress of the Doha Round, the major trading powers – first of all the United States and the European Union (EU) – are increasingly focussing on negotiating bilateral or regional trade agreements. Agreements such as the Trans-Pacific Partnership (TPP), which was signed on 4 February 2016 by the United States, Japan and 10 other Pacific countries, and the Transatlantic Trade and Investment Partnership (TTIP), which is currently under negotiation between the United States and the EU, cover large shares of global trade and investment flows and aim at regulating issues that go beyond the elimination of tariffs, such as investment, standards and the environment. At the same time, the main trading powers are promoting so-called plurilateral agreements that focus on specific topics. The most prominent example is the Trade in Services Agreement (TiSA), which is negotiated outside the WTO. We argue that the role of the WTO as the central organisation for the governance of world trade is weakened by this wave of mega-regional and plurilateral trade deals. Until now, reforms of the world trading system have only played a subordinate role at the G20 summits. The summit declarations contain only vaguely drafted commitments to strengthen the multilateral trading system, or commitments that bilateral, regional and plurilateral trade agreements should be complementary and in conformity with the rules of the WTO. We argue that the G20 should assume a more proactive role with regard to the future of the WTO and the reform of the world trading system. Such a reform is needed in light of the growing fragmentation of the system. At the same time, the 2030 Agenda for Sustainable Development of the United Nations calls for sustainability to be the core principle of global cooperation, including in the context of international trade. Among other things, the 2030 Agenda calls for “a universal, rules-based, open, non-discriminatory and equitable multilateral trading system under the World Trade Organization”. Bridging the gap between the realities of the international trading system and the aspirations of the 2030 Agenda is a formidable challenge that cannot be tackled effectively either in the context of the WTO or the UN and the 2030 Agenda alone. The G20 is a suitable forum to bridge that gap.
Keywords: 330; Handel und Investitionen; Regionale + globale + transnationale Governance